STOCK PRICES AND EXCHANGE RATE VARIABILITY IN NIGERIA ECONOMETRIC ANALYSIS OF THE EVIDENCE - Umoru, David; Asekome, Mike O. (European Scientific Journal, ESJ, 2013)
This study examines the dynamic interaction between stock prices and the Naira-US exchange rate in Nigeria using co-integration and the Granger-Sim causality methodology. The results portray the fact that whenever there is a change in the Naira-US exchange rate, stock prices react in tandem. The empirical analysis thus provides evidence of a positive co-integrating relationship between the Naira-US exchange rate movement and the Nigerian stock market prices with bi-directional Granger causality found to exist between stock prices and exchange rate in Nigeria during the period researched. The results accordingly lend empirical support to the fact that the Naira-US exchange rate movement and the Nigerian stock exchange market interacted in a manner that is simultaneously consistent with the predictions of the flow and stock theories.